The Effect of Zn Nanoparticle Concentration and the Comparison of Growth Regulator Concentration on the Growth of Cavendish Banana Explants (Musa acuminata) - Sarah Nurmala Putri Rukmana; Pangesti Nugrahani; Didik Utomo Pribadi (Edu Spectrum: Journal of Multidimensional Education, 2024)
Cavendish banana (Musa acuminata L.) propagation through conventional methods requires a considerable amount of time. Tissue culture techniques offer a more efficient alternative, enabling the production of plantlets with superior quality and quantity in a shorter period. The application of Zn nanoparticles has been shown to reduce media contamination and act as a biostimulant, enhancing propagation efficiency in tissue culture. Auxins, such as Naphthalene Acetic Acid (NAA), facilitate cell development and root induction, while cytokinins, including 6-Benzyl Amino Purine (BAP), are effective in stimulating cell division, morphogenesis, and shoot formation with improved stability and resistance to oxidation. This study was conducted from February to June 2023 at the Biotechnology Laboratory, Faculty of Agriculture, Universitas Pembangunan Nasional "Veteran" Jawa Timur. The research utilized a Completely Randomized Design (CRD) with two factors: the concentration of Zn nanoparticles and the ratio of ZPT concentrations. The results indicated that the best treatment for multiplication was obtained with 50 ppm Zn nanoparticles, resulting in the fastest shoot emergence at 24,63 days and the highest number of shoots per plantlet at 2,58 shoots. Furthermore, the treatment with a ZPT concentration ratio of NAA + BAP (0:0) produced the highest average number of plantlet leaves, with 5,78 leaves per plantlet.